PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA ANA JASA TITIP MANOKWARI) - Bajari, Makarius; Bopeng, Louis Soemadi; Mehue, Dorce Fransiska (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2024)
This study aims to analyze the variables of Service Quality, Trust and Price on Ana Jasa Titip Manokwari Consumer Satisfaction. This type of research used a qualitative approach with the type of associative problem. The population in this study are consumers from Ana Jasa Titip who have used Ana Jasa Titip two or more times and the total sample is 80 respondents using the purposive sampling method as the sampling method. Data collection methods use primary data, namely observation, interviews, questionnaires and secondary data, namely books, journals, articles and internet sites. The research instrument used a Likert scale with data analysis methods, namely multiple linear regression analysis. The results of this study indicate that the independent variables, namely service quality, trust and price have a partially significant effect on customer satisfaction and the results of simultaneous testing of the independent variables, namely service quality, trust and price simultaneously have an effect on Ana Jasa Titip's customer satisfaction.